AGRARIAN CONFLICT AND CIVIL LAW IN MANAGEMENT OF C OIL MINING IN THE BATANG TORU PROTECTED FOREST AREA SOUTH TAPANULI - Vivian Hasra Sitompul; Bastian Romual s; Muhammad Dzaky Epindo; Bambang Fitrianto (International Journal of Synergy in Law, Criminal, and Justice, 2025)
Management of Class C Mining in the Batang Toru protected forest area, South Tapanuli, is one of the crucial issues that triggers agrarian conflicts, especially related to the rights of customary law communities (MHA). This study aims to examine the civil law aspects in the management of Class C Mining and its implications for agrarian conflicts involving MHA. The agrarian conflict case in Batang Toru shows violations of civil regulations related to forest area use permits, business use rights, and utilization of natural resources. A descriptive qualitative approach is used in this study with a document analysis method of the National Inquiry report of the National Human Rights Commission and related government policies. The findings of this study indicate that agrarian conflicts in this area are driven by weak government supervision of the issuance of business permits, as well as rampant violations of MHA rights due to exploitation of natural resources that do not comply with legal procedures. The cases of PT. Gemala Borneo Utama and PT. Selantai Agro Lestari are real illustrations of how weak cross-sectoral government coordination has an impact on the sustainability of agrarian conflicts. In addition, the implementation of civil law in dispute resolution is still minimal due to the absence of cross-sectoral institutions that have full authority to handle agrarian conflicts comprehensively